Lyot-based Multi-wavelength Fiber Laser - Suhairie Saleh; N. A. Cholan; A. H. Sulaiman; M. A. Mahdi (International Journal of Electrical and Computer Engineering (IJECE), 2017)
A multi-wavelength fiber laser which is based on a Lyot filter is experimentally demonstrated. A combination of four-wave mixing in a highly nonlinear fiber and Lyot filter mechanism in the laser cavity is able to generate multi-wavelength with relatively high extinction ratio (ER). At the input current of 100mA, six laser lines with ER more than 5 dB are successfully generated. The wavelength spacing for the multi-wavelength is 0.15nm, corresponding to the characteristics of the Lyot filter used.